1999
DOI: 10.1111/j.1749-6632.1999.tb07790.x
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Signaling and Action in Fat Cells: Associations with Insulin Resistance and Type 2 Diabetes

Abstract: Adipose tissue only accounts for a relatively small proportion (< 10%) of the peripheral glucose utilization in response to insulin. However, the fat cells may still play an important role in insulin resistance and Syndrome X through, for instance, its endocrine functions (production of leptin, TNF alpha, PAI-1, etc.) and involvement in lipid metabolism (FFA release and hydrolysis of triglycerides). The fat cells are also highly sensitive to insulin and may thus be used to elucidate molecular mechanisms for in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0
5

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(68 citation statements)
references
References 27 publications
1
62
0
5
Order By: Relevance
“…Our model closely resembles the clinical and metabolic abnormalities seen in humans born at low birth weight and, furthermore, displays the phenotype of syndrome X (Reaven 1993, Smith et al 1999. Offspring develop profound hyperphagia, obesity, hypertension, hyperinsulinaemia and hyperleptinaemia during adult life and postnatal hypercaloric nutrition amplifies the metabolic and cardiovascular abnormalities induced by fetal programming (Vickers et al 2000).…”
Section: Introductionmentioning
confidence: 59%
“…Our model closely resembles the clinical and metabolic abnormalities seen in humans born at low birth weight and, furthermore, displays the phenotype of syndrome X (Reaven 1993, Smith et al 1999. Offspring develop profound hyperphagia, obesity, hypertension, hyperinsulinaemia and hyperleptinaemia during adult life and postnatal hypercaloric nutrition amplifies the metabolic and cardiovascular abnormalities induced by fetal programming (Vickers et al 2000).…”
Section: Introductionmentioning
confidence: 59%
“…It is known that IRS1 is reduced in adipose tissue from type 2 diabetic patients [20], and in healthy first-degree relatives of subjects with type 2 diabetes [21]. This suggests that the reduction in IRS1 is not a consequence of persistent hyperglycaemia or hyperinsulinaemia, but represents a very early defect that predisposes a person to type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this contention, Bogan and Lodish (43) have shown that secretion of adiponectin by 3T3-L1 adipocytes requires phosphatidylinositol 3-kinase (PI-3K), a major intermediate of insulin signaling activity. Insulinstimulated insulin receptor substrate 1 (IRS-1)-associated PI-3K activity has been shown to be decreased in adipocytes of type 2 diabetic subjects (44). Thus it is possible that the decreased adipocyte PI-3K activity in type 2 diabetic patients may contribute to the decreased adiponectin levels.…”
Section: Metabolic Roles Of Adiponectinmentioning
confidence: 99%